The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.35808/ijeba/304
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital as a Base for Regional Development: A Case Study

Abstract: The study uses the statistical method, the method of analogy and comparison, as well as the positive and normative approach. Findings: The study indicated that in the agricultural sector there are several problems associated with the formation of human resources. This is evidenced by the presence of negative trends that have been observed over the past 20 years. The main problems are the low educational level of workers, aging professional staff, and a reduction in the number of employees in all positions. Pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(25 reference statements)
0
9
0
1
Order By: Relevance
“…The prerequisites for the formation of protest including youth lumpenization and deprivation (inconsistency between the increased social expectations of young people and the real possibilities for their realization) were studied [9]. The manifestations of youth protestivity in the modern conditions increasingly acquiring the structure of network interaction were also examined.…”
Section: Resultsmentioning
confidence: 99%
“…The prerequisites for the formation of protest including youth lumpenization and deprivation (inconsistency between the increased social expectations of young people and the real possibilities for their realization) were studied [9]. The manifestations of youth protestivity in the modern conditions increasingly acquiring the structure of network interaction were also examined.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the learning outcomes, such ambassadors not only believe in the company, share its values, personally use its products or services and recommend it to others, but also have well-developed communication skills that help them "infect" others with their ideas. Secondly, based on current market development trends (Sycheva, 2019), the authors identified the main patterns in positioning a brand ambassador. The definition of this concept in the information field of social networks allowed the authors to get even closer to a common understanding and orientation in a wide mass media space.…”
Section: Discussionmentioning
confidence: 99%
“…Besides this, browsing algorithms are constantly changing in favor of personal accounts, and corporate site traffic is decreasing, hence making it necessary to promote each post for a fee so that even subscribers can view it. Company employees have personal pages on social networks and this can bring additional benefits to the company (Sycheva, 2019). Subsequent upon new forms of communication, an employee becomes an advertising medium and a brand conductor for consumers, otherwise known as a brand ambassador or a corporate ambassador.…”
Section: Introductionmentioning
confidence: 99%
“…Modern processes of growing global crises and rapidly developing digital transformations have significantly changed approaches to human capital research and articulated new public management objectives in this sphere. Of severe problems of human capital management in Russia a low level of the tools and approaches used for it can be noted, which leads to reduced efficiency and losses in human capital (Sycheva et al, 2019;Titova et al, 2019).…”
Section: Problem Statementmentioning
confidence: 99%